Effect of problem posing on problem-solving ability in mathematics learning of elementary school students - Witri Darlena; Agus Susanta; Irwan Koto; Edi Susanto (International Journal of Trends in Mathematics Education Research, 2022)
Preliminary survey data on students' problem-solving abilities in elementary schools in Bengkulu City showed low results. To achieve maximum mathematics learning outcomes, applying the right learning approach is necessary. This study aims to analyze the effect of problem-posing learning on students' problem-solving abilities. The research method used is quasi-experimental with a quantitative approach. The population in this study were all fifth graders of SD Negeri 5 Bengkulu City. The research sample was selected by purposive sampling, in which class VB was the experimental class, and VC was the control class, with 26 students each. Data collection is done by observation and tests. Data were analyzed using an independent statistical test t-test. The results showed an effect of problem posing on the problem-solving abilities of fifth-grade students at SDN 5 Bengkulu City. This is shown from the t-test results at the 95% confidence level with a statistical significance of 0.000 alpha (0.05). Problem posing is also effective in improving problem-solving ability, which is indicated by the N-gain value of 0.72 (high category).